Honey quality from the bee Apis cerana, honey potency produced by coconut and sugar palm saps - Erwan Erwan; Agussalim Agussalim (Society for Indonesian Biodiversity, 2022)
Abstract. Erwan, Agussalim. 2022. Honey quality from the bee Apis cerana, honey potency produced by coconut and sugar palm saps. Biodiversitas 23: 5854-5861. One of the big problems when keeping honeybees is the limited sustainable feed, especially in the rainy season. The objectives of this study were to evaluate the honey quality from the bee Apis cerana based on the chemical composition and honey potency produced by the coconut and sugar palm saps. This study using thirty colonies of the bee A. cerana was divided into six treatments consisting of sugar palm sap without sugar palm pollen, coconut sap without sugar palm pollen, coconut sap of 50% + sugar palm sap of 50% without sugar palm pollen, sugar palm sap was added by sugar palm pollen; coconut sap was added by sugar palm pollen; coconut sap of 50% + sugar palm sap of 50% was added by sugar palm pollen. The chemical composition of honey from the A. cerana was moisture (20.76 to 21.80%), reducing sugar (62.78 to 68.37%), sucrose (1.44 to 3.42%), diastase enzyme activity (5.17 to 9.04 DN), hydroxymethylfurfural (2.24 to 5.81 mg/kg), and acidity (26.00 to 36.33 mL NaOH/kg). Honey potency produced by the coconut and sugar palm saps in 100 hectares area produces honey was 1542.857 tons/year and 1150 tons/year, respectively. It can be concluded that the quality of A. cerana honey, produced by the sugar palm and coconut saps, is acceptable by the Indonesian national and international standards. The sugar palm and coconut saps have big potential as bee feed, especially for the bee A. cerana.